ANALISIS PARTISIPASI MASYARAKAT DAN MANFAAT PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT DI DESA MARANA KECAMATAN SINDUE KABUPATEN DONGGALA - Mulya, Djaya (Katalogis, 2016)
This study has several objectives to analyze: (1) the post-Pamsimas benefit, (2) public participation in the Pamsimas program; (3) the realtionship between individual characteristics variable and the level of community participation in Pamsimas in Marana village, Sindue District, Donggala Regency. This study apply descriptive analysis techniques as data analysis with average methods and Pearson Chi Square. The data in this study include primary data which were collected by delivered questionnaires. The results showed: (1) the level of benefit of post-Pamsimasis relatively high; (2) community participation in both categories reached 48.3 percent and less public participation category reached 51.7 percent; (3) public participation in exploiting the output of project is categorised as low; and (4) there is no big difference between the proportion of participation level by both good and less category based on individual characteristics, except for theage group of variable.